Implementasi Metode Simple Additive Weighting (SAW) Pada Sistem Informasi Evaluasi Kinerja Guru (Studi Kasus SMK Utama Bandar Lampung) - Dodi Afriansyah (Jurnal Teknologi dan Informatika (JEDA), 2020)
AbstrakEducation in Indonesia continues to improve throughout the 21st century. This is none other than because of the continuous evaluation of the education system which provides information on the lack of educational gaps and their renewal. Therefore, SMK Utama Bandar Lampung is present in the middle of the community at very affordable costs and is supported by qualified teachers or teachers. Each teacher or teacher conducts a process of selecting the best teachers to get qualified teaching staff. However, data management management of the achievement of the question has not yet been implemented to produce the right decision. This is because it takes time to process the results of questions and in the process of determining teacher performance it is possible for errors to occur. Based on this description, SMK Utama Bandar Lampung requires a decision support system that is expected to find solutions in the process of determining the best teacher. Assessment of decision systems that can facilitate the process of processing data on teacher performance assessment results in SMK Utama Bandar Lampung. Therefore, the researcher proposes a decision support system software engineering using Simple Additive Weighting (SAW). This system can be used to make it easier for students to assess teachers at SMK Utama Bandar Lampung, to help schools, especially principals, in evaluating the shortcomings and strengths of teacher performance at SMK Utama Bandar Lampung.